An evaluation framework and comparative analysis of the widely used learning management systems. - Adnan Abid; Abdullah Hassan Tufail; Osama Mohamed Ahmed Salem; Naeem A Nawaz; Uzma Farooq; Irfan Abid; Kashif Ishaq (PLoS ONE)
Learning Management System (LMS) is a major tool used in most universities and institutions for online/distance education purposes. A variety of LM systems are being used in different universities and institutions, and these LM systems are also updating their versions and patches to stay in the competition. Hence, the selection of an appropriate LMS is an important task as it is going to influence the academic proceedings of an academic institution. There are a few online comparison sheets available for different LMS, which have been scored based on online feedback, but those online comparisons lack a comprehensive features list for the comparison, and are unable to provide a generalized scoring function to compute the suitability score for an LMS. This article proposes a framework to evaluate an LMS based on a detailed list of features and functions. This evaluation is scored through a generalized scoring function that computes the quantitative score of LM systems. Lastly, some widely used open access and proprietary LM systems have been evaluated using the proposed framework and scoring function.